Salmonella spp. in RASFF notifications involving Croatia in the period from 01/01/2014 to 31/12/2018 - Friganović, Emilija (Array, 2019)
The Rapid Alert System for Food and Feed (RASFF) enables a fast exchange of information between bodies and institutions involved in the system (EU Member State national food safety authorities, Commission, EFSA, ESA, Norway, Liechtenstein, Iceland and Switzerland) in order to respond promptly to the health risks associated with food and feed. Salmonella is an important cause of EU foodborne outbreaks, most frequently reported pathogenic microorganism in food in the last few years. The aim of this study was to analyze RASFF notifications on food products contaminated with Salmonella spp. involving Croatia in the period from 01/01/2014 to 31/12/2018. All data were downloaded from the RASFF database (RASFF portal) and processed in MS Excel 2010. The collected data provided information on the: country(ies) of origin and distribution of the contaminated product, notifying country, product and product category, notification type, risk decision, action taken, distribution status and, for some incidents, a Salmonella spp. serovar. Notifications mainly concerned "poultry meat and poultry meat products". Just over half of the reported food products originated from Poland, Brazil and Italy. Croatia was notifying country in almost half of the published notifications. Majority of the notifications were classified as alert notifications and of serious risk. Most of the Salmonella spp. notifications were based on official controls on the market and on company's own check.